TRANSFORMASI PENDIDIKAN PESANTREN SEBAGAI LEMBAGA PENDIDIKAN ISLAM ABAD 21 - Faisal Kamal (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
Boarding school as early education institution characterized by an Indonesia (Wali Sanga era heritage), the institutional form of pesantren has undergone a change form. Today, pesantren as an Islamic institutions transform and showed rocketing shots made in the system changes. It looks at the elements such as pesantren educational objectives, curriculum, methods, and institutional management. An evolutionary change in boarding school, indeed confirms that the institution is not an old-fashioned boarding school and change. The attitude of the pesantren education system renew in precisely shows how the process of change is done carefully and meticulously. It proved to be nowadays more and more popping up pesantren an increasingly progressive in advancing their education system. This research specifically discuss how the process of institutional transformation of the pesantren education based on the study and analysis of libraries. As for the result is pesantren as an institution of Islam has been transformed and the changes that can be seen from the function of the pesantren as a social institution and as an educational institution